Pengaruh Rasio Hutang Terhadap Profitabilitas (Studi Pada Perusahaan Properti & Real Estate Terdaftar di Bursa Efek Indonesia Periode 2020) - Alma'uunah, Robii'ah; Mukaram (Jurnal Riset Bisnis dan Investasi, 2021)
The characteristics of the property as a product that does not depreciate raises speculation that property as a product will not end up as consumption, but an investment. However, sales that occur are not automatically recognized in the recording of financial statements after the application of PSAK 72. The application of PSAK 72 will at least affect the profits and debt levels of property companies because sales that have not been recognized will be included as current liabilities. In this study, the GPM (gross profit margin) ratio is used to determine the profit margin, ROA (return on assets) to determine the return on investment, and DR (debt ratio) to determine the amount of debt to total funding. The research methods used in this study include descriptive analysis, regression analysis, coefficient of determination analysis, and hypothesis testing. The results showed that debt ratio has a negative effect on profitability.